Determinants of self assessed health among Spanish older people living at home - Damian, J. (BMJ Group, 1999)
STUDY OBJECTIVE: To identify the main determinants of self assessed health among community dwelling elderly. PARTICIPANTS AND SETTING: A representative sample of 677 people aged 65 and over of the city of Madrid, Spain. DESIGN: Cross sectional study. Information was collected through personal interviews at the homes of the selected subjects. The five category dependent variable was grouped into two categories: good and poor self assessed health. Age, sex, social class, use of physician services, number of chronic conditions, and functional capacity, were included as main explanatory factors. Adjusted odds ratios were estimated through multiple logistic regression models. MAIN RESULTS: A total of 49.5% of subjects rated their health as good or very good. Those aged 85 and over rated their health higher than those aged 65-74 (adjusted odds ratio (OR): 0.37; 95% confidence intervals (CI): 0.18, 0.77). The adjusted OR for an increase of three chronic conditions was 3.48 (95% CI: 2.49, 4.85). Functional capacity also showed a strong independent effect (OR: 3.64; 95% CI: 1.89, 7.02). Social class was one of the main determinants for the youngest group, with those in the upper class reporting a better health perception (OR: 3.28 95% CI: 1.70, 6.35), but showed no effect in the oldest old (OR: 1.05; 95% CI: 0.57, 1.96). CONCLUSIONS: Age, chronic conditions, and functional status were the main determinants of perceived health among Spanish elderly. The effect of social class on perceived health markedly decreases with age. This study may contribute to a better utilisation and interpretation of self ratings in research and in general practice.